Peranan Sosio-Kultural Masyarakat dalam Reformasi Madrasah Swasta Menjadi Lembaga Persekolahan (Nurul Ulfatin, State University of Malang) - Nurul Ulfatin (Universitas Negeri Malang, 2016)
This study aimed to find out a substantive theory on the process of change of private madrasah, emphasizing personnel development and communities socio-cultural characteristics. The study implemented a qualitative approach at four private Madrasah Ibtidaiyahs (MISs). The result indicated that the MIS were firstly founded by kiais as informal and later became formal education institutions. The MISs were handled by teachers and foundations activists with special characteristics but without qualification as professional teachers, so that the MISs development was unique and less professional. The socio-cultural characteristics of the MISs were influenced by their socio-cultural environment so that the MISs development should be synchronized to the socio-cultural development.